2014
DOI: 10.1073/pnas.1403424111
|View full text |Cite
|
Sign up to set email alerts
|

Murine CD27 (−) Vγ6 (+) γδ T cells producing IL-17A promote ovarian cancer growth via mobilization of protumor small peritoneal macrophages

Abstract: Cancer-associated inflammation mobilizes a variety of leukocyte populations that can inhibit or enhance tumor cell growth in situ. These subsets include γδ T cells, which can infiltrate tumors and typically provide large amounts of antitumor cytokines, such as IFN-γ. By contrast, we report here that in a well-established transplantable (ID8 cell line) model of peritoneal/ovarian cancer, γδ T cells promote tumor cell growth. γδ T cells accumulated in the peritoneal cavity in response to tumor challenge and coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
199
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(218 citation statements)
references
References 69 publications
(107 reference statements)
9
199
1
Order By: Relevance
“…Pro‐tumour function of γδ 17 cells has been demonstrated in several cancer models, including a breast cancer metastasis model72 and an ovarian cancer model,73 and the roles of γδ 17 cells in the development of tumours have been reviewed elsewhere 74. Abundant γδ 17 cell infiltration accompanied by immunosuppressive myeloid‐derived suppressor cells is found in human colorectal cancer with positive correlation with advanced tumour clinicopathological features, suggesting that γδ 17 cells induce myeloid‐derived suppressor cell‐mediated immunosuppression 75.…”
Section: γδ17 Cells In Tumoursmentioning
confidence: 99%
“…Pro‐tumour function of γδ 17 cells has been demonstrated in several cancer models, including a breast cancer metastasis model72 and an ovarian cancer model,73 and the roles of γδ 17 cells in the development of tumours have been reviewed elsewhere 74. Abundant γδ 17 cell infiltration accompanied by immunosuppressive myeloid‐derived suppressor cells is found in human colorectal cancer with positive correlation with advanced tumour clinicopathological features, suggesting that γδ 17 cells induce myeloid‐derived suppressor cell‐mediated immunosuppression 75.…”
Section: γδ17 Cells In Tumoursmentioning
confidence: 99%
“…A subset of γδT cells that produces IL-17 (termed γδT17 cells) plays a pivotal role not only in protection against bacterial and fungal infection (1) but also in the progression of inflammatory disorders (2-4), tumor growth and metastasis (5)(6)(7)(8), and tissue regeneration (9). The cytokine-producing potential of γδT cells is programmed during their development in the thymus (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study suggested that TCRγδ-deficient mice display reduced tumor growth compared with wild-type animals (35). The different levels of CD3 and TCRγδ expression may indicate that in these two subsets, a variety of co-stimulatory signaling pathways could be involved in the regulation of activation and proliferation.…”
Section: Discussionmentioning
confidence: 98%